The april constitution and the continuity of the Polish state in exile - Szumiło, Mirosław (A thousand years of Poland’s presence among the elite of European states, 2026)
symbolicznej. 23:02 This article examines the role played by the constitutional act of April 23, 1935, known as the April Constitution, in ensuring the continuity of the Polish state in exile. Its provisions made it possible to preserve the continuity of statehood and the sovereignty of the Republic of Poland, which had been under double wartime occupation since September 1939. Following the seizure of power in Poland by the Communists — who in effect constituted an outpost of a foreign state — the Polish government in exile continued its activities after 1945. Standing firm on the principle of legalism, it based its authority on the April Constitution. Although it was not recognized on the international stage, it made possible the preservation of legal continuity between the Second and Third Polish Republics, at least in the symbolic sphere.